Influence of powdered and granular activated carbon system as a pre‐treatment alternative for membrane filtration of produced water. Issue 2 (3rd May 2016) - Kose‐Mutlu, Borte; Ersahin, Mustafa Evren; Ozgun, Hale; Kaya, Recep; Kinaci, Cumali; Koyuncu, Ismail
Abstract: BACKGROUND: Membrane technology is used for the treatment of produced water enabling high permeate quality to meet discharge standards or potable and irrigation water quality standards. In this study, the effect of hybrid membrane‐activated carbon processes on the performance of nanofiltration (NF) and reverse osmosis (RO) membrane systems treating mixed oil and gas field produced water was investigated. Different pre‐treatment alternatives including combinations of microfiltration unit and powdered activated carbon (PAC) or granular activated carbon (GAC) systems were applied prior to nanofiltration and reverse osmosis processes. RESULTS: The activated carbon process increased chemical oxygen demand (COD) and conductivity removal efficiencies due to the organic matter and ion adsorption capacity of activated carbon. PAC addition gave the best removal efficiencies for COD, whereas highest conductivity removals were obtained in studies with GAC addition. CONCLUSION: Differences obtained in the performance of different pre‐treatment alternatives based on targeted pollutants and membrane characteristics confirmed synergetic/antagonistic effects between pre‐ and final membrane treatment. © 2016 Society of Chemical Industry